1990
DOI: 10.3354/meps063239
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and activity of bacterio-plankton in the marginal ice zone of the Weddell-Scotia Sea during austral spring

Abstract: The distribution and metabolic actlvity of bactenoplankton were examined in relabon to b~ologlcal, chemical and physlcal factors in the marginal ice zone south of the confluence of the Weddell-Scotia Sea during austral spring 1983 Melt water produced by the seasonal retreat of the Ice edge resulted in regions of water wlth reduced salinity and increased vertical strabf~catlon, w h~c h in turn increased average irradiance levels for phototrophic growth The enhanced stability of the water column apparently influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 28 publications
(49 reference statements)
4
21
0
Order By: Relevance
“…We found an inverse pattern between these variables (compare Fig. 5 of Sullivan et al 1990 with Fig. 4 in this study).…”
Section: Patterns Of Microbial Biomass and Activity In Different Studsupporting
confidence: 75%
See 3 more Smart Citations
“…We found an inverse pattern between these variables (compare Fig. 5 of Sullivan et al 1990 with Fig. 4 in this study).…”
Section: Patterns Of Microbial Biomass and Activity In Different Studsupporting
confidence: 75%
“…In contrast, we found low values for abundance of heterotrophic microorganisms (bacteria and HNF) and BHP in this zone, compared to the other study zones (Table 1). Sullivan et al (1990) found higher heterotrophic microbial activity and biomass in the ice edge surrounding waters up to 200 km northward. These authors also found a significant correlation between bacterioplankton and phytoplankton (activity and biomass) along a transect from the IEZ to the open sea.…”
Section: Patterns Of Microbial Biomass and Activity In Different Studmentioning
confidence: 83%
See 2 more Smart Citations
“…Low-temperature suppression of bacterial growth has not been universally observed. For example in Antarctica, bacterial growth rates of ca 0.01 to 2 d-' have been reported at -1.5"C (Hanson et al 1983, Kottmeier et al 1987, Kottmeier & Sullivan 1988, Cota et al 1990, Rivkin 1991. In the North Bering and Chukchi Seas, bacteria grew at 0.1 to 0.54 d-' at < l°C (Anderson 1988) and in Resolute, NWT, Canada, sea ice bacterial growth rates were 0.02 to 0.25 d-' at -1.7"C (Smith et al 1989, Smith & Clement 1990.…”
Section: Introductionmentioning
confidence: 99%